Intestinal butyric acid-mediated disruption of gut hormone secretion and lipid metabolism in vasopressin receptor-deficient mice - Kazuki Harada; Eiji Wada; Yuri Osuga; Kie Shimizu; Reiko Uenoyama; Masami Yokota Hirai; Fumihiko Maekawa; Masao Miyazaki; Yukiko K. Hayashi; Kazuaki Nakamura; Takashi Tsuboi (Molecular Metabolism)
Objectives: Arginine vasopressin (AVP), known as an antidiuretic hormone, is also crucial in metabolic homeostasis. Although AVP receptor-deficient mice exhibit various abnormalities in glucose and lipid metabolism, the mechanism underlying these symptoms remains unclear. This study aimed to explore the involvement of the gut hormones including glucagon-like peptide-1 (GLP-1) and microbiota as essential mediators. Methods: We used the mouse GLP-1-secreting cell line, GLUTag, and performed live cell imaging to examine the contribution of V1a and V1b vasopressin receptors (V1aR and V1bR, respectively) to GLP-1 secretion. We next investigated the hormone dynamics of V1aR-deficient mice (V1aR−/− mice), V1bR-deficient mice (V1bR−/− mice), and V1aR/V1bR-double deficient mice (V1aR−/− V1bR−/−mice). Results: AVP induced the increase in intracellular Ca2+ levels and GLP-1 secretion from GLUTag cells in a V1aR and V1bR-dependent manner. AVP receptor-deficient mice, particularly V1aR−/−V1bR−/− mice, demonstrated impaired secretion of GLP-1 and peptide YY secreted by enteroendocrine L cells. V1aR−/−V1bR−/−mice also exhibited abnormal lipid accumulation in the brown adipose tissue and skeletal muscle. We discovered that V1aR−/− V1bR−/− mice showed increased Paneth cell-related gene expression in the small intestine, which was attributed to increased fecal butyric acid levels. Exposure to butyric acid reduced GLP-1 secretion in L cell line. Additionally, human Paneth cell-related gene expressions negatively correlated with that of V1 receptor genes. Conclusions: The deficiency in V1 receptor genes may increase gut butyric acid levels and impair the function of L cells, thus dysregulating lipid homeostasis in the brown adipose tissue and skeletal muscle. This study highlights the importance of appropriate control of the gut microbiota and its metabolites, including butyric acid, for the optimum functioning of enteroendocrine cells.